Pelaku Usaha dan Riba Study Kasus di Kota Batam - awi, masni awi; Amrizal, Amrizal (Faculty of Social Science, Universitas Negeri Padang, 2023)
This research aims to determine the impact of businesses with usury capital for business actors in Batam City. This research uses a qualitative method with a case study type, data was collected using an interview guide. The research presents the results of interviews, observations, documentation and is tested using the triangulation method. The results of this research show that there are negative impacts from business actors who use usurious capital. This impact can be avoided by: Opening/starting a business with capital that comes from good sources and avoiding usury loans, providing productive opportunities to the community through fund-collecting institutions, providing education to the community through da'wah.